Experimental Study on Frost Resistance of Nano-silicon Oxide-Rubber Recycled Concrete - LIU Liu (Renmin Zhujiang)
To study the frost resistance of nano-silicon oxide-rubber recycled concrete,this paper prepares the recycled concrete,with the substitution rate of recycled coarse aggregate and recycled fine aggregate of 30%,that of natural river sand by rubber powder of 0,1%,3%,5%,etc.and that of cement by nano SiO2 of 0%,1.5% and 3.0% respectively,and conducts the freeze-thaw cycle test of nano-silicon oxide and rubber powder recycled concrete with different content.The experimental results show that:After addition of rubber powder and nano-SiO2,the frost resistance of recycled concrete is improved.As the freeze-thaw cycles reach 50,and the content of rubber powder and nano-SiO2 is 5% and 3% respectively,the improvement on the frost resistance of recycled concrete is the best,and the strength loss rate is 45.5% lower than that of ordinary concrete.